PELAKSANAAN PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT DI DESA LUBUK MAYAN KECAMATAN RANTAU PANDAN KABUPATEN BUNGO PROVINSI JAMBI - Nurhidayati Amelia; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Implementation of supplying water and sanitation based society program is a program and government’s real action (center and region) for increasing society’s health degree especially in decreasing diarrhea disease rate and other disease which transmitted through water and environment. Lubuk Mayan Village till now is not avalaible supplying clean water system, where the condition supplying water system which ever exist by other program which from Rantau Duku Village now has not distributed again to Lubuk Mayan Village ofteThe theory concept that used is empowerment. For analyzing implementation of supplying water and sanitation based society program, researcher used theory of Delivery. The researcher used qualitative research with descriptive method. In collecting data, researcher used key informant as information source and triangulation technique as source in validity test.The result of research shows that implementation of supplying water and sanitation based society program in Lubuk Mayan village have proceed suitable with regulation and plan that exist. In implementation of supplying water and sanitation based society program are enthusiastic to contribute in empowerment process.Key Words : Implementation, Water and sanitation, Public Empowerment